Koegzystencja z miastem zagrożeniem dla tożsamości wsi podmiejskich na przykładzie dawnej wsi Morasko koło Poznania - Dymek, Dominika; Bednorz, Leszek (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
This paper aims to evaluate the preservation state of the traditional landscape forms of Morasko, a former village near Poznań. In the Poznań agglomeration, constant development has been taking place since the end of the 1990s , resulting in obliteration of agrarian culture, degradation of the suburban village landscape and spatial chaos. As a result of the strong urbanization pressure, Morasko has become the northern district of Poznań, part of the Morasko-Radojewo housing estate. The formerly distinct settlement structure has visibly undermined. The agricultural area has shrunk, replaced by residential and recreation and service areas. The new buildings do not correspond with the landscape. Against all these odds, the remains of the former grange culture of Morasko are still visible in the degraded suburban landscape.
Keywords: suburban village; suburbanization; urban sprawl; place identity; Morasko; Poznań